Regulation of Proinflammatory Molecules and Tissue Factor by SARS-CoV-2 Spike Protein in Human Placental Cells: Implications for SARS-CoV-2 Pathogenesis in Pregnant Women - Guo, Xiaofang; Semerci, Nihan; De Assis, Viviana; Kayisli, Umit A.; Schatz, Frederick; Steffensen, Thora S.; Guzeloglu-Kayisli, Ozlem; Lockwood, Charles J. (Frontiers in Immunology, 2022)
SARS-CoV-2 infects cells via binding to ACE2 and TMPRSS2, which allows the virus to fuse with host cells. The viral RNA is detected in the placenta of SARS-CoV-2-infected pregnant women and infection is associated with adverse pregnancy complications. Therefore, we hypothesize that SARS-CoV-2 infection of placental cells induces pro-inflammatory cytokine release to contribute to placental dysfunction and impaired pregnancy outcomes. First, expression of ACE2 and TMPRSS2 was measured by qPCR in human primary cultured term cytotrophoblasts (CTBs), syncytiotrophoblast (STBs), term and first trimester decidual cells (TDCs and FTDCs, respectively), endometrial stromal cells (HESCs) as well as trophoblast cell lines HTR8, JEG3, placental microvascular endothelial cells (PMVECs) and endometrial endothelial cells (HEECs). Later, cultured HTR8, JEG3, PMVECs and HEECs were treated with 10, 100, 1000 ng/ml of recombinant (rh-) SARS-CoV-2 S-protein ± 10 ng/ml rh-IFNγ. Pro-inflammatory cytokines IL-1β, 6 and 8, chemokines CCL2, CCL5, CXCL9 and CXCL10 as well as tissue factor (F3), the primary initiator of the extrinsic coagulation cascade, were measured by qPCR as well as secreted IL-6 and IL-8 levels were measured by ELISA. Immunohistochemical staining for SARS-CoV-2 spike protein was performed in placental specimens from SARS-CoV-2–positive and normal pregnancies. ACE2 levels were significantly higher in CTBs and STBs vs. TDCs, FTDCs and HESCs, while TMPRSS2 levels were not detected in TDCs, FTDCs and HESCs. HTR8 and JEG3 express ACE2 and TMPRSS2, while PMVECs and HEECs express only ACE2, but not TMPRSS2. rh-S-protein increased proinflammatory cytokines and chemokines levels in both trophoblast and endothelial cells, whereas rh-S-protein only elevated F3 levels in endothelial cells. rh-IFNγ ± rh-S-protein augments expression of cytokines and chemokines in trophoblast and endothelial cells. Elevated F3 expression by rh-IFNγ ± S-protein was observed only in PMVECs. In placental specimens from SARS-CoV-2-infected mothers, endothelial cells displayed higher immunoreactivity against spike protein. These findings indicated that SARS-CoV-2 infection in placental cells: 1) induces pro-inflammatory cytokine and chemokine release, which may contribute to the cytokine storm observed in severely infected pregnant women and related placental dysfunction; and 2) elevates F3 expression that may trigger systemic or placental thrombosis.